Macronutrient self-selection in dogs and the impact on markers of health : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Roberts, Mark (Massey University, 2020)
Dogs represent the only large carnivore to have been domesticated. By inheriting wolf ancestry, the domestic dog has retained several carnivorous traits, with for example teeth adapted for grasping and tearing a prey item. Both protein and fat are essential to the dog, but not carbohydrate. However, the most popular feeding option for a modern dog is a dry, extruded diet, with carbohydrate representing a major macronutrient. It is also apparent that domesticated dogs are currently eating diets that differ substantially from what their ancestors consumed. Based on this, the aim of this PhD was to determine what macronutrient intake dogs target, if given the option to select. Further investigations would then examine the impact of the diet selected on health. The first of the four studies involved dogs fed ad libitum for a ten-day duration. Three diets, involving a protein-fat-carbohydrate (PFC) metabolisable energy (ME) ratio of 18%:28%:54% (high carbohydrate HC), 13%:86%:1% (high fat HF) and 57%:42%:1% (high protein HP) were offered. The overall mean macronutrient intake of the dogs was PFC 34%:63%:3% (ME). However, over the duration of the study, fat intake (ME) decreased significantly (62% to 51% ME) and protein increased (34% to 45% ME). After completing this study, a follow on experiment was conducted to determine if ingredients or macronutrients were the key determinate in what a dog decides to eat. This question was answered by providing the animals with two HC diets (PFC 18%:28%:54% ME), but with different key carbohydrate sources (extruded maize or rice). The same method was again used, but this time with two HP diets (PFC 34%:66%:0% ME) and either lamb green tripe or venison meat being the main protein sources. The results shown that no significant difference in intake between both the two high carbohydrate and the two high protein diets was detected, thus macronutrient content was crucial to palatability. On completing this investigation, it was therefore decided to expand the initial study, to clarify the macronutrient selection had stabilised, this time over 28 days. This additionally provided the opportunity to assess the faecal microbiota and metabolites of the animals. The results showed of the third study showed that the dogs consumed a very similar macronutrient intake to the initial study (PFC: 34%:62%:4% ME). Moreover, differences in faecal microbiota and metabolomic data were apparent from when the dogs consumed a baseline extruded diet, to selecting a diet dominated by fat and protein. As the dogs had previously selected a high fat diet, typically associated with increasing the risk of pancreatitis, it was decided that the final study should involve investigating biomarkers of pancreatitis in dogs previously fed a baseline commercial extruded diet, before suddenly consuming a high fat meal. This was followed by switching either to a HF or HC diet for eight weeks and repeating the same measurements and consuming a final high fat meal. Although both the HC and HF diet fed dogs highlighted no meaningful differences in biomarkers of pancreatitis, differences were apparent with the baseline diet. A key factor was triglycerides, with both the HC and HF diet fed dogs that consumed the final HF meal having significantly lower (P<0.001) peak triglyceride values (1.51 mmol/L and (1.49 mmol/L) compared to dogs that had consumed the baseline diet (2.52 mmol/L). As both the baseline extruded and HC diets comprised of a similar macronutrient ratio (baseline diet PFC 23:26:52 ME and HC diet PFC 17%:32%:51%ME), other aspects likely had an influencing role. These include moisture, ingredients, level of diet processing, and possibly digestibility. In conclusion, this thesis has shown that a high fat meal fed to a healthy dog presents no detectable risk to health compared to being fed a high carbohydrate, low fat diet. In addition, a high fat diet has also been demonstrated to be more palatable than carbohydrate-based diets, typically seen in commercial extruded products. Finally, although the feeding of a HF meal to a dog did not increase the risk of pancreatitis per se, if a commercial extruded diet was fed prior, it does increase risk factors. As this response was not witnessed with a non-extruded HC diet, determining what factors in an extruded diet potentially increase the risk of pancreatitis if suddenly switched to a HF diet, should be the focus of future research.
Figures 1.2 (=Akers & Denbow, 2008 Fig 17.7 p.491) and 1.5 (=Raubenheimer et al., 2009 Fig 4(d) & Denno & Fagan, 2003 Fig 2C) have been removed for copyright reasons.
Keywords: Dogs; Food; Nutrition; Fat content; 300303 Animal nutrition